Media Literacy Approach in Islamic Religious Education Curriculum for the Digital Era - Nova Mei Devi; Juliani; Nova Kemala Syahputri; Nadia Nurul Hasanah (Yayasan Zia Salsabila, 2023)
The rapid development of the digital era has significantly impacted various aspects of life, including education. In the context of Islamic Religious Education (PAI), the challenges of the digital age necessitate approaches that equip students with critical and wise skills to navigate the flow of information. This study aims to explore the implementation of a media literacy approach within the PAI curriculum. The primary focus is to analyze how media literacy can help students understand, evaluate, and utilize digital media in alignment with Islamic values. Furthermore, this study seeks to formulate effective teaching strategies to address digital issues such as misinformation, negative content, and radicalism while fostering strong Islamic character. The findings are expected to contribute to the development of a PAI curriculum that is both relevant to the challenges of the digital age and applicable at the elementary school level.